Optimisation of a sol–gel synthesis route for the preparation of MgF2 particles for a large scale coating process. Issue 45 (24th September 2015) - Scheurell, K.; Noack, J.; König, R.; Hegmann, J.; Jahn, R.; Hofmann, Th.; Löbmann, P.; Lintner, B.; Garcia-Juan, P.; Eicher, J.; Kemnitz, E.
Abstract : Preparation of transparent and low viscous MgF2 sols via sol–gel technique which can be applied for antireflective coatings on glass substrates is described. Abstract : A synthesis route for the preparation of optically transparent magnesium fluoride sols using magnesium acetate tetrahydrate as precursor is described. The obtained magnesium fluoride sols are stable for several months and can be applied for antireflective coatings on glass substrates. Reaction parameters in the course of sol synthesis are described in detail. Thus, properties of the precursor materials play a crucial role in the formation of the desired magnesium fluoride nanoparticles, this is drying the precursor has to be performed under defined mild conditions, re-solvation of the dried precursor has to be avoided and addition of water to the final sol-system has to be controlled strictly. Important properties of the magnesium fluoride sols like viscosity, particle size distribution, and structural information are presented as well.